Critical or Conformist Economic Education? Reflexivity Versus Functionality in the Conflict of Interests - Fridrich, Christian (Critical Education)

(untitled) (Institute for Critical Education Studies / UBC, 2025)
This article focuses on an essential element of economic education, namely the ability to think critically. First, the significance of education and empowerment is discussed in relation to the two levels of subject and society. Subsequently, the educational intentions in the two fundamental paradigms of economic education are characterized, namely in socio-economic education and in economistic education. In these, reflexivity and functionality are expressed in different ways: either as the implementation or negation of critical approaches. As a result, criticism, the ability to think critically and a reflexive basic attitude of young people are either promoted or suppressed. This has significant consequences for students’ understanding of themselves and the world. Based on a differentiated concept of the ability to think critically (according to Hedtke, 2023a), facets of critical or uncritical economic and financial education are analyzed in a differentiated manner in relation to the subject level and the societal level in a four-field diagram developed from this. Finally, implementations of critical economic education and their opponents are discussed using Austria as a case study.